Therapeutic Effects of Specialized Pro-Resolving Lipids Mediators on Cardiac Fibrosis via NRF2 Activation - Gyeoung Jin Kang; Eun Ji Kim; Chang Hoon Lee (MDPI AG, 2020)
Heart disease is the number one mortality disease in the world. In particular, cardiac fibrosis is considered as a major factor causing myocardial infarction and heart failure. In particular, oxidative stress is a major cause of heart fibrosis. In order to control such oxidative stress, the importance of nuclear factor erythropoietin 2 related factor 2 (NRF2) has recently been highlighted. In this review, we will discuss the activation of NRF2 by docosahexanoic acid (DHA), eicosapentaenoic acid (EPA), and the specialized pro-resolving lipid mediators (SPMs) derived from polyunsaturated lipids, including DHA and EPA. Additionally, we will discuss their effects on cardiac fibrosis via NRF2 activation.